Natural Bioactive Compounds Promote Cell Apoptosis in Gastric Cancer Treatment: Evidence from Network Pharmacological Study and Experimental Analysis - Yan Wang; Haiyang Wang; Shun Xu (Journal of Chemistry)
Background. Gastric cancer (GC) is one of the most lethal cancers. Shenlian capsule (SLC) is a Chinese patent medicine made from 11 herbs containing numerous plant-derived compounds, and the clinical trials of SLCs confirmed that they had effective adjuvant therapy for a variety of cancer such as lung cancer and gastric cancer. Moreover, the HPLC fingerprint of SLCs was established from other research to find potential components. In this study, network pharmacology-based research was used to identify combinations with molecules, targets, and pathways to explore their interaction mechanisms. Methods. The Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and the Traditional Chinese Medicine Integrated Database (TCMID) were widely implemented in selecting the active chemical components of SLCs with an oral bioavailability (OB) ≥ 30% and drug-likeness (DL) ≥ 18%. In addition, the TCMSP and TCMID databases obtained the targets of SLCs, and PharmMapper (PM) was used to predict targets of SLCs. Gastric cancer-related genes were provided by the GeneCards and TTD databases. Subsequently, the drug/target/pathway network was established and visualized using Cytoscape software. Then, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genome (KEGG) enrichment analyses were used to predict the potential genes and pathways of gastric cancer. Molecular docking was performed to study the interaction between ligands and targets; the interaction was visualized using Discovery Studio and PyMOL. Finally, the potential primary mechanism used by SLCs against gastric cancer was verified by cell experiments, including MTT cell apoptosis assay, flow cytometry cell cycle assay, and western blotting with HGC-27 cells (undifferentiated). Results. Of 213 active chemical components from SLCs, 35 primary active chemical components were identified, and 10 potential critical targets were selected from the 185 intersections of the targets of SLCs and GC, such as RAC-alpha serine/threonine kinase 1 (AKT1), cellular tumor antigen p53 (TP53), interleukin-6 (IL6), caspase-3 (CASP3), vascular endothelial growth factor A (VEGFA), and epidermal growth factor receptor (EGFR). GO and KEGG enrichment analysis provided the PI3K/AKT, TNF, and p53 signaling pathways, which may be the primary signaling pathways modulating gastric cancer. Molecular docking verified targets such as AKT1, TP53, EGFR, and CASP3, which exhibited satisfactory binding capacity with active ingredients. Experiments with HCG-27 cells confirmed that SLCs may provide favorable treatment for GC by promoting CASP3 and TP53 expression to induce cell apoptosis and provided the predictions for network pharmacology and molecular docking. MTT and flow cytometry assays verified that SLCs promoted cell apoptosis and inhibited cell proliferation by triggering G0/G1 and S cell cycle arrest. In addition, western blot analysis confirmed that SLCs promoted TP53 and CASP3 overexpression, which led to HGC-27 gastric cell apoptosis. Conclusions. Our results confirmed that SLCs inhibit proliferation of HGC-27 gastric cell by promoting cell apoptosis and, therefore, have potential in the treatment of advanced gastric cancer. P53 signaling pathway was the key pathway. In addition, quercetin, matrine, and ursolic acid might be the main active ingredients.